Simultaneous targeting of VEGF-receptors 2 and 3 with immunoliposomes enhances therapeutic efficacy. (2nd January 2016) - Orleth, Annette; Mamot, Christoph; Rochlitz, Christoph; Ritschard, Reto; Alitalo, Kari; Christofori, Gerhard; Wicki, Andreas
Abstract: Background : Tumor progression depends on angiogenesis. Vascular endothelial growth factor (VEGF) receptors (VEGFRs) are the main signal transducers that stimulate endothelial cell migration and vessel sprouting. At present, only VEGFR2 is targeted in the clinical practice. Purpose : To develop new, anti-angiogenic nanoparticles (immunoliposomes, ILs), that redirect cytotoxic compounds to tumor-associated vascular cells. Methods : Pegylated liposomal doxorubicin (PLD) was targeted against VEGFR2- and VEGFR3-expressing cells by inserting anti-VEGFR2 and/or anti-VEGFR3 antibody fragments into the lipid bilayer membrane of PLD. These constructs were tested in vitro, and in vivo in the Rip1Tag2 mouse model of human cancer. Results : The combination treatment with anti-VEGFR2-ILs-dox and anti-VEGFR3-ILs-dox was superior to targeting only VEGFR2 cells and provides a highly efficient approach of depleting tumor-associated vasculature. This leads to tumor starvation and pronounced reduction of tumor burden. Conclusion : Nanoparticles against VEGFR2 and −3 expressing tumor-associated endothelial cells represent a promising and novel anti-cancer strategy.